PENGARUH E-WOM DAN INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND TRUST SEBAGAI VARIABEL MODERASI - Djami Rane, Melvin Krisdiana; T.A.Ledo, Diani.; Yeni, Yeni; Ramdhani, Miftah Faiz Ali; Husen, Syamsier (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the influence of E-WOM and influencers on purchasing decisions with brand trust as a moderating variable. This study uses a quantitative method, and data are collected through questionnaires and literature studies. The study population includes 150 consumers, with sample selection based on specific criteria. Data analysis involves a series of tests, including validity tests, reliability tests, descriptive statistical tests, and classical assumption tests. Hypotheses are tested using multiple linear regression analysis and Moderated Regression Analysis (MRA) to understand the role of moderating variables. The results of this study indicate that Partially, E-WOM has a significant effect on purchasing decisions. Influencers have a significant effect on purchasing decisions. Simultaneously, E-WOM and influencers have a significant effect on purchasing decisions. Brand trust negatively and significantly moderates the influence of influencers on purchasing decisions. Brand trust negatively and significantly moderates the influence of E-WOM on purchasing decisions.